998. Clinical Outcomes and Cost Savings of Dalbavancin Use in OPAT: Focus on Complicated Staphylococcus aureus Infections. (15th December 2022) - Alexander, Bryan T; Miller, Molly M; LeMaster, Melissa; Bergman, Scott J; Van Schooneveld, Trevor C; Cortes-Penfield, Nicolas W
Abstract: Background: The practical and financial benefits of long-acting glycopeptides are increasingly recognized, and their efficacy is becoming better established for a variety of indications. Dalbavancin use as primary therapy for complicated Staphylococcus aureus (cSA) infections, however, has only been described in small case series to this point. Methods: This retrospective review identified patients prescribed dalbavancin for any indication and followed by the Nebraska Medicine OPAT team since program implementation (4/1/19 - 4/30/22). Patients in the cSA infection subgroup were defined by need for >2 weeks of treatment for a Staphylococcus aureus infection involving bacteremia. Dalbavancin as primary therapy for cSA was defined as initiation of dalbavancin within the first 10 days of antibiotic therapy and continued through the end of treatment. The primary clinical outcome was 30-day readmission rate (both infection-related and not infection-related). Results: A total of 66 patients were prescribed dalbavancin for treatment of any infection (Table 1), with an all-cause 30-day readmission rate of 13.6% (9 of 66); only two of these were infection-related (3%). Updating a prior institutional analysis, use of dalbavancin led to the avoidance of 506 planned inpatient days per year on average and $1, 113, 000 in yearly inpatient costs. Dalbavancin was utilized for primary therapy of cSA in 16 patients, of whom only one (6.3%) had a 30-day readmission, due to progression of cSA vertebral osteomyelitis-discitis. Table 1: Characteristics of the Dalbavancin Cohort Conclusion: In both overall and cSA subgroup analysis, OPAT use of dalbavancin was associated with low readmission rates. This study is the largest to date suggesting favorable clinical outcomes with dalbavancin as primary therapy for cSA infections; others have reported few of these patients or utilized dalbavancin exclusively as consolidation therapy following significant lead-in with other antimicrobials. The enrolling Dalbavancin as an Option for Treatment of Staphylococcus aureus Bacteremia study (DOTS; NCT04775953) is anticipated to provide randomized controlled data evaluating this approach. Discharge facilitation utilizing dalbavancin contributed significantly to OPAT program cost justification and resources to support team expansion. Disclosures: Bryan T. Alexander, PharmD, BCIDP, AAHIVP, Astellas Pharma: Advisor/Consultant Scott J. Bergman, PharmD, BCIDP, FCCP, FIDSA, Merck & Co., Inc: Advisor/Consultant|Merck & Co., Inc: Grant/Research Support|Merck & Co., Inc: Honoraria|Pfizer: Advisor/Consultant|Pfizer: Honoraria Trevor C. Van Schooneveld, MD, bioMerieux: Advisor/Consultant|bioMerieux: Grant/Research Support|Insmed: Grant/Research Support|Merck: Grant/Research Support|Thermo-Fischer: Advisor/Consultant.